Apuntes sobre la representación de lo político - Nemrava, Daniel (Verbum – Analecta Neolatina, 2014)
Based on the idea of Adorno’s impossibility to narrate and to represent freedom because of the split between “experience” and “narration” of history, we offer a reading of Manuel Puig focusing on how its narrative thematizes this crisis in a specific social and political context. Accepting the possibility of the dialectical relationship between “experience” and “history”, and considering the “history” as a structure of “experience”, we are allowed to analyze the mode and character of the structuring of this “experience” and the meaning and message of the dialectical relationship between the entities concerned. From Puig’s narratives we have chosen the novel El beso de la mujer araña (The Kiss of the Spider Woman). Through its protagonist, the author narrates imaginary displacements at various levels, especially “border territories” or “transition zones”, and he creates “maps” from the cell, interconnecting multiple fields in the sense of rhizomatic mapping. In this dynamic of “journeys” which determines the existence of the subjects, we are revealed deeper meanings concerning Argentinean social and political reality.